Effective Dose Rate Coefficients for Immersions in Radioactive Air and Water. Issue 2 (5th May 2016) - Bellamy, M. B.; Veinot, K. G.; Hiller, M. M.; Dewji, S. A.; Eckerman, K. F.; Easterly, C. E.; Hertel, N. E.; Leggett, R. W.; Manger, R.
Abstract: The Oak Ridge National Laboratory Center for Radiation Protection Knowledge (CRPK) has undertaken a number of calculations in support of a revision to the United States Environmental Protection Agency (US EPA) Federal Guidance Report on external exposure to radionuclides in air, water and soil (FGR 12). Age-specific mathematical phantom calculations were performed for the conditions of submersion in radioactive air and immersion in water. Dose rate coefficients were calculated for discrete photon and electron energies and folded with emissions from 1252 radionuclides using ICRP Publication 107 decay data to determine equivalent and effective dose rate coefficients. The coefficients calculated in this work compare favorably to those reported in FGR12 as well as by other authors that employed voxel phantoms for similar exposure scenarios.